2017
DOI: 10.1186/s12872-017-0650-y
|View full text |Cite
|
Sign up to set email alerts
|

Surface ECG interatrial block-guided treatment for stroke prevention: rationale for an attractive hypothesis

Abstract: Atrial fibrillation (AF) is the most common sustained arrhythmia and is associated with stroke, cognitive impairment, and cardiovascular death. Some predisposing factors − as aging, diabetes, hypertension − induce and maintain electrophysiological and ultrastructural remodeling that usually includes fibrosis. Interatrial conduction disturbances play a crucial role in the initiation of atrial fibrosis and in its associated complications. The diagnosis of interatrial blocks (IABs) is easy to perform using the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 30 publications
1
19
0
5
Order By: Relevance
“…IAB has been described to predict occurrence of new onset and recurrent AF. A disturbed interatrial conduction, as in IAB, results in varying/shorter refractory periods and slower conduction velocities within the atrial myocardium-a potential substrate for the development of atrial arrythmias (5)(6)(7).…”
Section: Ecg Description and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IAB has been described to predict occurrence of new onset and recurrent AF. A disturbed interatrial conduction, as in IAB, results in varying/shorter refractory periods and slower conduction velocities within the atrial myocardium-a potential substrate for the development of atrial arrythmias (5)(6)(7).…”
Section: Ecg Description and Discussionmentioning
confidence: 99%
“…Anti-arrhythmic treatment of patients with aIAB has shown to reduce AF occurrence, however; no randomized data are available at the present time (6). Furthermore, IAB is highly prevalent in patients with embolic stroke (5,6,8,9). In patients with aIAB, due to a block of impulse propagation between the atria, depolarization follows a caudo-cranial route, first towards the AV node and then in a retrograde direction through the left atrium (3) (Figure 3), resulting in poor left atrial electromechanical function (6).…”
Section: Ecg Description and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Исследования взаимосвязи межпредсердной блокады и эмболического инсульта привели к обсуждению возможности применения антикоагулянтов с целью профилактики инсульта у пациентов высокого тромбоэмболического риска с далеко зашедшей межпредсердной блокадой даже при отсутствии фибрилляции предсердий [47,51,52]. Кроме того, основанием для идеи применения антикоагулянтов у пациентов без…”
Section: межпредсердная блокада и наджелудочковые аритмииunclassified
“…Bayés syndrome is currently defined as the finding of advanced interatrial block (a-IAB) on 12-lead ECG associated with atrial fibrillation (AF) (1). Several studies have demonstrated the high risk of developing atrial fibrillation for patients with a-IAB, which has practical consequences of anticoagulant administration (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%